Is Demonstrating Understanding Rewarding? Student Academic Performance and Student Expression Mode in the Context of Micro Differentiation - van Braak, Marije (Student Undergraduate Research E-journal!, 2015)
High-performing students receive higher levels of micro differentiation (i.e., higher quality of tailored support) compared to low-performing students [1]. The present study investigated an explanation for this practically relevant finding, hypothesizing that high-performing students utilize more demonstrations of understanding than claims of understanding compared to low-performing students. Thereby, they enable better teacher assessment of students’ needs, thus eliciting higher levels of micro differentiation. Research methods included coding scheme development and correlational analysis. Results revealed no evidence for the hypothesized relation between student academic performance and student expression mode. Findings of subsequently conducted exploratory analyses indicate important directions for future work.